ENHANCING PROBLEM-SOLVING SKILLS IN ELEMENTARY STUDENTS THROUGH REALISTIC MATHEMATICS EDUCATION - SUSANTI, ERMA (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
Realistic Mathematics Education (RME) is an innovative approach aimed at enhancing students' problem-solving skills by connecting mathematical concepts to real-world contexts. Traditional mathematics education often focuses on rote memorization and abstract procedures, leaving students disengaged and unable to apply their knowledge effectively. RME addresses this gap by emphasizing context-based learning, student-centered exploration, and progressive mathematization, fostering critical thinking and conceptual understanding. This study examines the implementation of RME through literature reviews and case studies from schools worldwide. Methods include analyzing research findings on the impact of RME on student outcomes, including test scores, engagement, and confidence.  Results indicate that RME significantly improves problem-solving skills, with students in RME classrooms outperforming peers in traditional settings. Enhanced engagement and confidence in mathematics were also observed, particularly in scenarios where students collaboratively tackled realistic problems. However, challenges such as resource constraints, teacher preparation, and curriculum adaptation remain. The findings underscore RME’s transformative potential in mathematics education. Schools and policymakers are encouraged to adopt RME, supported by targeted professional development and further research to refine and innovate its practices. ABSTRAKRealistic Mathematics Education (RME) adalah pendekatan inovatif yang bertujuan untuk meningkatkan keterampilan pemecahan masalah siswa dengan menghubungkan konsep matematika ke konteks dunia nyata. Pendidikan matematika tradisional sering kali berfokus pada hafalan dan prosedur abstrak, yang menyebabkan siswa kurang terlibat dan tidak mampu menerapkan pengetahuan mereka secara efektif. RME mengatasi kesenjangan ini dengan menekankan pembelajaran berbasis konteks, eksplorasi yang berpusat pada siswa, dan matematisasi progresif, sehingga mendorong pemikiran kritis dan pemahaman konseptual. Penelitian ini mengkaji penerapan RME melalui tinjauan literatur dan studi kasus dari sekolah-sekolah di seluruh dunia. Metode yang digunakan termasuk menganalisis temuan penelitian tentang dampak RME terhadap hasil belajar siswa, termasuk skor tes, keterlibatan, dan kepercayaan diri. Hasil menunjukkan bahwa RME secara signifikan meningkatkan keterampilan pemecahan masalah, di mana siswa di kelas RME menunjukkan kinerja yang lebih baik dibandingkan dengan teman-teman mereka dalam pengaturan tradisional. Peningkatan keterlibatan dan kepercayaan diri dalam matematika juga diamati, terutama dalam skenario di mana siswa secara kolaboratif menyelesaikan masalah realistis. Namun, terdapat tantangan seperti keterbatasan sumber daya, persiapan guru, dan adaptasi kurikulum. Temuan ini menegaskan potensi transformasi RME dalam pendidikan matematika. Sekolah dan pembuat kebijakan didorong untuk mengadopsi RME, didukung oleh pengembangan profesional yang terarah dan penelitian lebih lanjut untuk menyempurnakan dan menginovasikan praktiknya.